Pentagon's South Asia defence and strategic year book, 2010 - Singh, Harjeet; Raju, M.M. Pallam (New Delhi : Pentagon Security International, 2010)
South Asia's complex geopolitical realities present a number of challenges to regional countries and dominate the discourse. Likewise, there are complex geostrategic issues which inhibit regional cooperation and add to trust-deficit. This 2010 volume captures the perspectives of experts and scholars on South Asia who offer insights of the region.
Keywords: National security -- South Asia -- Periodicals; South Asian cooperation -- Periodicals; South Asia -- Defenses -- Periodicals